Increasing The Competitiveness Of Food MSMEs Through Diversification, Innovation, And Creativity, In Gemah District, Semarang City - Nurchayati Nurchayati; Sukardi Sukardi; Suparmi Suparmi; Hikmah Hikmah; Tri Ratnawati, Andalan (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service aims to increase the competitiveness of cassava-based food MSMEs in Gemah Village through innovation, diversification, and creativity approaches. In this effort, training is carried out to diversify products and encourage innovation and creativity in the presentation of traditional foods. The training also covers digital marketing and branding strategies to increase product visibility online. It is hoped that through these concrete steps, food MSMEs in Gemah Village can optimize the potential of local raw materials, create diverse products, and increase competitiveness in an increasingly tight market. The sustainability of this business will be maintained through community networks and ongoing support, making a positive contribution to local economic growth and the welfare of the Gemah Village community.